Nanas of Sila : a compositional reflection about an Inuit conception - Avila, Alejandra Pineda De, 1984- (2017)
Nanas of Sila is a concert evening of southern lullabies developed in the eight following movements: The Hunt, The Death, The Confusion, The Renunciation, The Devotion, The Healing, The Return and The Transformation. It is a Performance-Composition that enhances the relationship of inside and outside. The movement oscillation, the complexity of overlapping rhythms and natures musical harmonies are traduce into the music of the human cradle. Rhythm, movement, poetry and melodies are performed by the musicians and create a landscape of the Inuit conception Sila. This project is the result of my two-year residency in Iceland, my confrontation with the Nordic nature and my encounter with the Inuit tradition. The music is a result of a larger framework "VIOLETT". “VIOLETT” is my artistic research on the reflection on music seen as a transitory object. My personal situation, singularity and environmental experiences, orients this compositional cycle and the meaning it generates. Keywords: Lullabies, Transitional Phenomenae, Sila